Squamous cell carcinoma arising in a pilonidal sinus presenting with the formation of an abscess. Issue 685 (November 1982) - Jamieson, N. V.; Goode, T. B.
Abstract : A case of squamous cell carcinoma arising in a pilonidal sinus and presenting with abscess formation is described and the treatment is discussed.